The European toolkit for ensuring the quality of pedagogical education at the end of the 20th – beginning of the 21st century: challenges for Ukraine - Postrygach, N. (New Collegium, 2022)
Over the past decades, the international recognition of the importance of professional training and development of teachers has led to a significant improvement and increase in the quality of the educational process in educational institutions. At the same time, the goal of professional growth of teachers in each country was determined in its own way, and the principles of functioning of its organizational models were characterized by considerable diversity. In Europe, there is still no unified system of institutional evaluation of the activities of educational institutions, similar to the accreditation system in the USA. However, each country has its own approaches to ensuring and assessing the quality of pedagogical education. The European toolkit for ensuring the quality of pedagogical education in the late 20th and early 21st centuries and its influence on the improvement of the domestic system of pedagogical education is analyzed. It is determined that the study of the experience of professional training of teachers in foreign countries opens new opportunities for the improvement of the pedagogical education system in Ukraine in the conditions of its adaptation to the requirements of the European educational space. It has been proven that the general directions of ensuring the quality of pedagogical education in the countries of the European Community and Ukraine are: preparation of teachers for educational reform, consolidation of organizational structures in the field of professional development and rationalization of national systems of pedagogical education; improvement of the quality of professional training and improvement of teachers; focusing attention on all-European joint events in the field of professional development of teachers. It has been established that the key provisions of international and pan-European documents actually include a joint program of actions to improve the quality of pedagogical education, in which teachers are considered as the main agents of change in the implementation of the pan-European strategy for the development of education and training, the development of the European area of pedagogical education and its formation on this basis. global model of a modern teacher.